Towards a Managed Learning Environment in Medical Education: Sheffield’s story - Roberts, Chris; Lawson, Mary; Newble, David; Self, Ashley (Proceedings of the International Conference on Networked Learning, 2002)
The University of Sheffield Medical School is undergoing a major revision of its medical curriculum in the light of reviews by both the professional regulatory body, the General Medical Council (GMC) and by the QAA. A networked learning environment has been developed in conjunction with other medical schools, which aims to facilitate, manage and support the delivery of the curriculum to medical students at their respective universities. The Sheffield NLE is considered central to the medical school’s plan to implement and evaluate the new curriculum.